Modelamento Prosódico para Conversão de Texto-Fala do Português Falado no Brasil DOI: 10.14209/jcis.1995.2 - H. da Silva, C.; Violaro, F. (Journal of Communication and Information Systems, 2015)
This paper describes a prosodic model for a text-to-speech synthesis system developed for the portuguese language spoken in Brazil. The model provides both a duration and a fundamental frequency (pitch) control of the phones. The model is based on rules extracted from a corpus of natural speech (phrases spoken by people). These rules control the duration of the phones and define fundamental frequency profiles for neutral declarative sentences.